The Impact of Personal Service, Product Quality, and Comfort on Guest Satisfaction at Yanyan Resort Ubud - I Ketut Susila; Luh Komang Candra Dewi; I Gede Anindya Perdana Putra; Alma Vorfi Lama (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to examine the influence of personal service, product quality, and comfort on guest satisfaction at Yanyan Resort Ubud, Bali-a competitive hospitality destination renowned for its cultural and natural appeal. Employing a quantitative descriptive approach, data were collected through structured questionnaires distributed to 50 resort guests. The analysis used multiple linear regression after conducting validity, reliability, and classical assumption tests. The results demonstrate that personal service, product quality, and comfort each have a significant and positive effect on guest satisfaction, both individually and collectively. Specifically, personalized attention, well-maintained facilities, and a tranquil environment were key drivers of a satisfactory guest experience. These findings suggest that sustained improvements in service quality, infrastructure, and environmental comfort can substantially enhance guest satisfaction. The study provides practical implications for hospitality managers, recommending regular staff training, continuous facility upgrades, and a strong emphasis on cleanliness and guest-centered services. By implementing these strategies, resorts like Yanyan Resort Ubud can foster customer loyalty, generate positive word-of-mouth, and improve long-term competitiveness in the tourism industry. Keywords: personal service, product quality, comfort, satisfaction